Pakistan : a hard country - Lieven, Anatol (New York : PublicAffairs, 2011)
In this profound and sophisticated analysis of Pakistan's history and its social, religious and political structures, Lieven argues strongly against U.S. actions that would risk destroying that state in the illusory search for victory in Afghanistan
Part 1: Land, people, history. Introduction : understanding Pakistan ; The struggle for Muslim South Asia -- Part 2: Structures. Justice ; Religion ; The military ; Politics -- Part 3: The provinces. Punjab ; Sindh ; Balochistan ;The Pathans -- Part 4: The Taleban. The Pakistani Taleban ; Defeating the Taleban? -- Glossary -- Appendix 1: Chronology of Muslim South Asia -- Appendix 2: Pakistani statistics
Includes bibliographical references (pages 496-505) and index
Keywords: Pakistan -- Politics and government -- 1988-; Pakistan -- Social conditions -- 21st century; Pakistan -- History